Profile of Hirschsprung’s disease cases diagnosed in tertiary care teaching hospital: a retrospective observational study - Prabakaran, S.; Thilagam, K. Kasthuri (International Journal of Contemporary Pediatrics, 2020)
Background: To date, there are very few studies of Hirschsprung’s disease. Hence, the study was conducted to profile Hirschsprung’s disease in a tertiary care setting. Methods: This is a retrospective observational study that evaluated the admitted patients with Hirschsprung’s disease in the pediatric surgery department. Biopsy was taken from the patient in the form of the full thickness of intestine, seromuscular biopsy, resection from the colostomy site when doing closure and or appendix was taken and subjected to histopathological study with routine eosin and haematoxylin stain. Results: Among the study population, 21(28.8%) children were aged less than one month, and only 10(13.7%) were aged 11 years and above. There were 45(61.6%) participants were male and 28(38.4%) female. Most common biopsy site was appendix in 33(46.2%), followed by Ileum full-thickness biopsy in 6(8.2%) , Ileum Seromuscular biopsy in 5(6.8%%) ,Colon full-thickness biopsy in 4(5.6%) subjects. Among the 73 participants, 46(63%) were clinically suspected cases, and the remaining 27(36.9%) were clinically established cases. Among clinically suspected, the majority (50.7%) had ganglionic cells only in proximal segments. Conclusions: the Hirschsprung's disease diagnosis was established mostly in younger males.